Targeting chromatin remodelers: Signals and search mechanisms - Erdel, Fabian; Krug, Jana; Längst, Gernot; Rippe, Karsten (Biochimica et biophysica acta. Gene regulatory mechanisms, 2011)
Chromatin remodeling complexes are ATP-driven molecular machines that change chromatin structure by translocating nucleosomes along the DNA, evicting nucleosomes, or changing the nucleosomal histone composition. They are highly abundant in the cell and numerous different complexes exist that display distinct activity patterns. Here we review chromatin-associated signals that are recognized by remodelers. It is discussed how these regulate the remodeling reaction via changing the nucleosome substrate/product binding affinity or the catalytic translocation rate. Finally, we address the question of how chromatin remodelers operate in the cell nucleus to find specifically marked nucleosome substrates via a diffusion driven target location mechanism, and estimate the search times of this process. This article is part of a Special Issue entitled:Snf2/Swi2 ATPase structure and function.
Gesehen am 29.04.2022